Development of an Injection Molded Boot Adapter - Forsgren, Lilian (My University, 2016)
A boot adapter is an injection moulded polymer component intended to isolate a spark plug in a combustion engine used in heavy vehicles. The boot adapter failed too fast either by cracking or electrical puncture and there were large variations of quality among the produced parts. The aim of this project was to reduce or eliminate the risk for the early function failure of the part by finding the cause of failure and developing effective, easy methods for quality assurance. From gathering data and information from previous testing and employees at the company, a number of hypotheses were set and the most probable once was evaluated through a failure analysis. To find a correlation between an easily measurable parameter and the performance of the piece, a number of tests were preformed where the investigation regarded how the weight of the boot adapter corresponded to its performance both thermally and electrically.
Keywords: Materialvetenskap; Innovation och entreprenörskap (nyttiggörande); Maskinteknik; Materialteknik; Materials Science; Innovation & Entrepreneurship; Mechanical Engineering; Materials Engineering